2003
DOI: 10.1002/jat.901
|View full text |Cite
|
Sign up to set email alerts
|

Putative role of proteolysis and inflammatory response in the toxicity of nerve and blister chemical warfare agents: implications for multi‐threat medical countermeasures

Abstract: Despite the contrasts in chemistry and toxicity, for blister and nerve chemical warfare agents there may be some analogous proteolytic and inflammatory mediators and pathological pathways that can be pharmacological targets for a single-drug multi-threat medical countermeasure. The dermal-epidermal separation caused by proteases and bullous diseases compared with that observed following exposure to the blister agent sulfur mustard (2,2'-dichlorodiethyl sulfide) has fostered the hypothesis that sulfur mustard v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 96 publications
2
27
1
Order By: Relevance
“…Animal experiments showed that PARP inhibition and/or boosting of NAD+ levels can reduce SM induced pathology, suggesting that PARP inhibitors may be used as a medical countermeasure for SM related injuries (Cowan et at., 2003;Gross et al, 1985;Mol et al, 1991 ;Yourick et at., 1991Yourick et at., , 1993Zhang et al, 69 1995 ). Regarding the mechanism of action of such a treatment, it bas been suggestion, that PARP inhibition induces a switch in the mode of cell death by inhibiting necrosis but driving cells into apoptosis, which, in combination with inhibition ofNF KB related gene transcription, counteracts SM induced inflammatory responses (Bai and Virag, 2012a;Kehe et al, 2008;Meier and Millard, 1998;Rosenthal et al, 2001 ).…”
Section: Parp Inhibitors Should Be Considered With Caution As a Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments showed that PARP inhibition and/or boosting of NAD+ levels can reduce SM induced pathology, suggesting that PARP inhibitors may be used as a medical countermeasure for SM related injuries (Cowan et at., 2003;Gross et al, 1985;Mol et al, 1991 ;Yourick et at., 1991Yourick et at., , 1993Zhang et al, 69 1995 ). Regarding the mechanism of action of such a treatment, it bas been suggestion, that PARP inhibition induces a switch in the mode of cell death by inhibiting necrosis but driving cells into apoptosis, which, in combination with inhibition ofNF KB related gene transcription, counteracts SM induced inflammatory responses (Bai and Virag, 2012a;Kehe et al, 2008;Meier and Millard, 1998;Rosenthal et al, 2001 ).…”
Section: Parp Inhibitors Should Be Considered With Caution As a Treatmentioning
confidence: 99%
“…Based on the rationale that PARP inhibition preserves NAD + levels and counteracts inflammation, PARP inhibitors were tested as potential therapeutic agents for SM exposures. Interest ingly, in several animal models PARP inhibition and/or boosting of NAD + synthesis led to reduced pathological signs upon SM exposure (Cowan et al, 2003;Gross et al, 1985;Mol et al, 1991;Yourick et al, 1991Yourick et al, , 1993Zhang et al, 1995). Despite previous reports on the effect of PARP inhibitors on SM induced NAD + depletion, cell death and pathology, specific reports characterizing the actual PARylation response upon mustard treatment are incomplete and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of cell viability in HD-exposed tissues may require the use of combined therapy with scavengers such as dimercaprol and with anti-inflammatory compounds such as octyl homovanillamide, both of which have proven effective in reducing HD-induced pathology in the mouse ear model (Cowan et al, 2003;Dillman et al, 2006). The combination of the anti-inflammatory compounds diclofenac and dexamethasone has been reported by Dachir et al (2004) to be particularly effective in that model.…”
Section: Discussionmentioning
confidence: 97%
“…It will be interesting to apply the optimized methodology as established in this work to study the PARylation response in cells treated with bifunctional sulfur and nitrogen mustards. This will have significant implica tions towards the question if PARP inhibitors may be used as a therapeutic option to mitigate SM induced pathologies, as suggested by several animal studies (Cowan et al, 2003;Gross et al, 1985;Mol et al, 1991;Yourick et al, 1991Yourick et al, , 1993Zhang et al, 1995) or to sensitize cancer cells to nitrogen mustard treatment, as tested in preclinical and clinical settings (Donawho et al, 2007;Norris et al, 2014). Several of these aspects are addressed in in an accompanying article (c.f.…”
Section: Discussionmentioning
confidence: 99%
“…Interest ingly, PARP inhibition did not influence cell survival in general, but shifted the mode of cell death, from necrotic to apoptotic cell death (Kehe et al, 2008;Meier et al, 1987;Papirmeister et al, 1985). It has been hypothesized that this shift is responsible for reduced mustard induced pathologies under conditions of PARP inhibition in a rodent animal model (Cowan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%